A Theory of Responsibility in Organizations - Prendergast, Canice J. (Journal of Labor Economics, 1995)
This article considers the implications of allowing a manager discretion over task assignment. If employees earn rents from carrying out tasks, and the manager cannot "sell" the jobs to her subordinates, she has an incentive to take on more tasks than is optimal and delegate too few to a subordinate. I show that although firms can alleviate this incentive by offering output-contingent contracts, even with the optimal contract, (i) the manager carries out too many tasks, (ii) she exerts too much effort on her own tasks, and (iii) her subordinate exerts too little effort on his tasks.